PREVALANCE OF ACUTE HEPATITIS IN DENGUE FEVER (The Research of Medical Science Review, 2025)
Background: Dengue fever, a mosquito-borne viral illness, has emerged as a major public health concern in tropical and subtropical regions. Among its various systemic complications, hepatic involvement is frequently observed, ranging from mild transaminase elevation to acute hepatitis. This study aims to determine the prevalence of acute hepatitis among patients diagnosed with dengue fever. Methods: A cross-sectional observational study was conducted on 150 patients admitted with confirmed dengue fever over a 6-month period at a tertiary care hospital. Dengue infection was diagnosed via NS1 antigen and/or IgM antibody testing. Acute hepatitis was defined as serum alanine aminotransferase (ALT) or aspartate aminotransferase (AST) levels elevated to more than 10 times the upper limit of normal. Liver function tests were performed on all patients upon admission and monitored throughout hospitalization. Results: Out of 150 dengue patients, elevated liver enzymes were found in 91 (60.7%) patients, and they were further divided into mild, moderate and severe derangement. Abdominal ultrasound showed increased hepatic echotexture in 26.6% and periportal fibrosis in 24.6% Based on biochemical parameters i.e. raised liver enzymes, acute hepatitis was found in 91 (60.7%) patients, and according to radiological studies, acute hepatitis was present in 106 (70.6%) patients. Conclusion: The study highlights that acute hepatitis is a common complication in dengue fever, Routine liver function monitoring in dengue cases is crucial for early identification and management of hepatic involvement, which may contribute to improved clinical outcomes.